2018
DOI: 10.1111/bjop.12284
|View full text |Cite
|
Sign up to set email alerts
|

Prospective emotion enables episodic prospection to shift time preference

Abstract: The episodic effect suggests that episodic prospection (imagining future events) can effectively reduce time discounting, the propensity to discount the value of delayed rewards relative to immediate ones. However, less clear is how episodic prospection modulates time preference. As engagement in episodic prospection usually evokes prospective emotions, it was proposed that episodic prospection might work by inducing prospective emotions. Although one previous study has attempted to provide evidence to the emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
60
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 38 publications
10
60
1
1
Order By: Relevance
“…Previous research have shown that positive affect may improve inhibitory control (Kuhl & Kazén, ). Similarly, positive prospection decreases time discounting, whereas negative prospection increases time discounting (Zhang, Peng, Qin, Suo, & Feng, ). The processes associated with planning future events may have less positive affect associated to them than the actual event itself.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research have shown that positive affect may improve inhibitory control (Kuhl & Kazén, ). Similarly, positive prospection decreases time discounting, whereas negative prospection increases time discounting (Zhang, Peng, Qin, Suo, & Feng, ). The processes associated with planning future events may have less positive affect associated to them than the actual event itself.…”
Section: Discussionmentioning
confidence: 99%
“…In the episodic cue (compared to the standard) task, individuals' preferences shifted towards future rewards, and the reduction of DD rates was associated with the vividness of the imagined future event and with increased functional coupling between the hippocampus and vmPFC and ACC regions associated with reward processing and valuation (Kable and Glimcher, 2007;Peters and Büchel, 2010;Benoit et al, 2011). The effect of episodic cueing on DD is consistently found in healthy individuals (Benoit et al, 2011;Liu et al, 2013;Lin and Epstein, 2014;Bromberg et al, 2017;O'Donnell et al, 2017O'Donnell et al, , 2018Zhang et al, 2018;Bulley et al, 2019), as well as patients with substance abuse disorders (Daniel et al, 2013;Snider et al, 2016), in whom it extends to real-world indices of impulsive choice, such as impulsive drinking or eating (Daniel et al, 2013;Dassen et al, 2016; see also Wu et al, 2017). In contrast, consistent with Peters and Büchel's (2010) finding that episodic cueing effects on DD are conditional upon the imagination of vivid future events, no episodic cueing effect has been observed in amnesic patients with hippocampal damage (Palombo et al, 2014; but see Kwan et al, 2015), who cannot construct detail-rich future events (Race et al, 2011;see also De Luca et al, 2018) to use for decisions.…”
Section: Introductionmentioning
confidence: 96%
“…One view is that the vivid imagination of future events triggers emotions in the here-and-now (Gilbert and Wilson, 2007;Damasio, 2009), rendering future rewards more emotionally engaging and desirable, and therefore capable to compete for salience with rewards that are available immediately (Boyer, 2008;Ciaramelli and di Pellegrino, 2011;. There is some evidence, indeed, that positive but not negative episodic future thinking reduces DD (Liu et al, 2013;Zhang et al, 2018), although other research using large samples has detected episodic cueing effects even following neutral (Lin and Epstein, 2014) and even negative future thinking (Bulley et al, 2019). Episodic future thinking may also alter participants' time perspective (Lin and Epstein, 2014), increase personal connectedness to the future (O'Donnell et al, 2017), and promote a more concrete and detailed construal of future events (Cheng et al, 2012;Lebreton et al, 2013), biasing choice accordingly.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the primary goals of this study were to examine whether EFT induced lower discounting rate compared to episodic recent thinking (ERT) in schizotypy and whether it was related to the magnitude of reward. Given previous studies have consistently shown that positive EFT significantly reduced discounting rate, while the effect of negative EFT was inconsistent (Bulley et al, 2019;Calluso, Tosoni, Cannito, & Committeri, 2019;Liu, Feng, Chen, & Li, 2013;S. Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, previous studies indicated that discounting rate varied with the magnitude of rewards, a lower discounting rate was observed in the larger magnitude condition (Green & Myerson, 2004;Kwan et al, 2012). However, most of the previous studies examining the effect of EFT on delay discounting included only one reward magnitude condition (Snider et al, 2016;Stein et al, 2016Stein et al, , 2017S. Zhang, Peng, Qin, Suo, & Feng, 2018), and the magnitude of delayed reward varied from study to study (Snider et al, 2016;Stein et al, 2016Stein et al, , 2017, e.g., in some studies the delayed larger reward was fixed $100 (Snider et al, 2016;Stein et al, 2017), while in some studies the magnitude of reward was fixed $1,000 (Stein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%